Il Rilievo fotogrammetrico con il Drone alla Diga di Ridracoli - Barberini, Marco; Rubboli, Matteo (GEOmedia, 2016)
SAPR technology integrates well with other technologies for survey activities in morphologically complex areas. In this article is presented a case study carried out for the photogrammetric documentation of Ridracoli Dam (Forli Cesena) In Italy.